Going for brokerage: strategies and strains in commercial healthcare facilitation - Benjamin M. Hunter (BMC, 2020)
Abstract Background The formation of domestic and global marketplaces during the past 50 years has opened up new commercial opportunities for third-party activity in healthcare systems. Commercial mediation of access to healthcare is one recent area of activity that sees companies and individuals offering to organise healthcare and travel in return for payment. With varying degrees of control over the location, type, cost and experiences of healthcare provisioning, these intermediaries occupy potentially influential positions in healthcare systems and yet much of their work is poorly understood. Methods Drawing on social science theories of brokerage, this article presents a novel analysis of commercial healthcare facilitation. It focuses on facilitation companies and their workers as central, intermediating actors for people to access healthcare in markets characterised by complexity. Semi-structured interviews were conducted with people working in domestic and international healthcare facilitation in London and Delhi, and data were analysed using a framework approach that emphasises the structural features and personal agencies for this area of work. Results Findings point to an institutional environment for commercial healthcare facilitation marked by competition and the threat of obsolescence. The activities of rivals, and the risk that users and providers will bypass intermediaries, compels facilitation companies to respond strategically and to continuously pursue new populations and activities to mediate - to go for broke. These pressures percolate into the lives of people who perform facilitation work and who describe a physical and mental burden of labour incurred by onerous processes for generating and completing facilitation work. The need for language interpretation services introduces an additional set of relations and has created further points of tension. It is an environment that engenders mistrust and anxiety, and which incentivises exploitation and a commodification of users whose associated commissions are highly prized. Conclusion Brokerage analysis provides valuable insights into the strategies and strains for commercial mediation of access to healthcare, and the findings indicate opportunities for further research on the contributions of interpreters, diplomatic and business networks, and new technologies, and on the growth of new forms of mediation in domestic and overseas settings.